PERANCANGAN E-BUSSINES PADA USAHATANI RAKYAT BERWAWASAN KERAJINAN LIMBAH AKAR WANGI (Vetiveria zizanioides (L.) Nash) GARUT JAWA BARAT - dewi, Ine shinta; Latifah, Retno; Prasetyaningrum, Putri Taqwa (Jurnal Sistem Informasi dan Bisnis Cerdas, 2020)
Fragrant root is a plant that can produce fragrant root oil through the distillation process. Indonesia is one of the largest producers of fragrant root oil in the world, the center of producing fragrant root oil in Indonesia is in Garut Regency. From the results of the study, in addition to producing pure oil, fragrant root waste can also be processed into handicrafts of secondary needs such as bags and souvenirs by weaving   DOI : https://doi.org/10.33005/sibc.v13i1.1721